2020
DOI: 10.22435/mpk.v30i1.434
|View full text |Cite
|
Sign up to set email alerts
|

Pemberdayaan Kader Gemari dalam Meningkatkan Pengetahuan dan Sikap Ibu Usia Remaja terhadap Perencanaan Keluarga di Kabupaten Bengkulu Tengah

Abstract: Abstract More than 50% of marriages in Bengkulu Province are adolescents marriages (less than 20 years). Adolescents marriage affects low levels of education, high incidence in the household, overcoming health problems, health problems in struggling children and psychological health of children because mothers of adolescents are less capable of planning a family. Therefore, community participation is needed to increase the knowledge and attitudes of adolescent mothers in family planning, namely through e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The final model shows that WCBA who married at the age of children, primiparous mothers, birth spacing, and mothers who had one toddler in the family were associated with poor Child Feeding practice after controlling for maternal work factors. The research in Bengkulu Utara Regency found that mothers who married in their teens had poor knowledge and attitudes about family planning (Simbolon et al, 2020). Mothers married at a young age have less understanding of marriage, fertility, and reproductive health problems (Erulkar, years and more than five years is a protection factor against poor Child Feeding practices.…”
Section: Resultsmentioning
confidence: 99%
“…The final model shows that WCBA who married at the age of children, primiparous mothers, birth spacing, and mothers who had one toddler in the family were associated with poor Child Feeding practice after controlling for maternal work factors. The research in Bengkulu Utara Regency found that mothers who married in their teens had poor knowledge and attitudes about family planning (Simbolon et al, 2020). Mothers married at a young age have less understanding of marriage, fertility, and reproductive health problems (Erulkar, years and more than five years is a protection factor against poor Child Feeding practices.…”
Section: Resultsmentioning
confidence: 99%
“…Untuk mengoptimalkan pemberdayaan remaja, perlu mendapat bantuan dan kerja sama diantaranya adalah dari kader. Salah satu penelitian menunjukkan bahwa pendampingan kader dapat meningkatkan pengetahuan dan sikap ibu usia remaja tentang perencanaan keluarga (Simbolon et al, 2020). Berdasarkan masalah di atas, maka untuk mencapai tujuan yaitu mencegah terjadinya pernikahan usia dini dan meningkatkan keaktifan remjaa serta mitra (kader dan karang taruna) dalam peningkatan kesehatan remaja, khususnya terkait masalah pernikahan usia dini, maka dianggap penting untuk melakukan kegiatan pengabdian masyarakat terkait upaya pencegahan usia pernikahan usia dini melalui pemberdayaan remaja dengan melibatkan kader dan karang taruna.…”
Section: A Latar Belakangunclassified